Evaluating Workflow Automation Efficiency in A Government Agency in the Philippines - Cabaobao, Jr., Andresito A.; Malubag, Sushmita L.; Briones, Jesus; Abante, Marmelo V. (International Journal of Entrepreneurship and Sustainability Studies, 2024)
Workflow automation plays a vital role in developing efficient government operations. Anchored on the Technology Acceptance Model, this descriptive-correlational study evaluated the efficiency of using automation tools in key work processes of a Philippine government agency. A census of the population was used to gather data from the 31 employees directly involved in the subject agency’s automation processes. Data were collected through a researcher-structured, validated questionnaire via Google Forms. These data were analyzed using frequency, percentage, weighted mean, multiple linear regression, ANOVA and Pearson r correlation analysis. The findings indicated that automation tools significantly enhanced the efficacy of key work processes in terms of speed, accuracy, and collaboration. Moreover, the study also revealed that employees are generally satisfied with performing routine and repetitive tasks because of the benefits of automation tools. However, the efficacy of key work processes is not significantly related to their overall job satisfaction. The study also revealed that the perceived impact of automation tools on key work processes is not affected by the demographic profile of the employees. This study also revealed that staff resistance and system integration issues are major barriers to the adoption of workflow automation. Furthermore, the study confirmed that there was no statistically significant correlation between perceived ease of use and problems encountered with automation tools.  A strategic roadmap is proposed to improve workflow automation efficiency and address adoption-related challenges. This study also offers valuable insights for other government agencies seeking to introduce and assess similar technologies to enhance workflow and operational efficiency.